Pengaruh Pembekalan dan Motivasi Kerja Terhadap Kinerja Mitra Badan Pusat Statistik Kabupaten Madiun (Studi Empiris Pada Mitra BPS Sensus Ekonomi 2016, Kecamatan Geger, Kabupaten Madiun.) - Yuchep Budi Prayogo; Aglis Andhita Hatmawan (UNIVERSITAS PGRI MADIUN, 2017)
The purpose of this research is to know the influence of Working Guidance and Motivation on Performance of Central Bureau of Statistics of Geger, Madiun Regency Partially, and which variable is the most dominant influence on employee performance. Respondents in this study amounted to 83 people. Data collection techniques used were observations, interviews and questionnaires. Data analysis techniques used are multiple linear analysis and hypothesis testing. Based on the results of partial data analysis found that there is a positive and significant influence between job training and work motivation variables on the performance of officers at BPS Partners in the Economic Census 2016 Geger District, Madiun District. Thus it is evident that there is a positive and significant effect of job training and work motivation on performance at the Economic Census 2016 Geger District. So it can be concluded that job training and work motivation. Proved able to improve the performance of officers in the Economic Census 2016 Geger District, Madiun District. Keywords: Debriefing, Work Motivation, Performance